The Role of Intracellular and Extracellular Vesicles in the Development of Therapy Resistance in Cancer - Wilczak, Magdalena; Surman, Magdalena; Przybyło, Małgorzata (Current Pharmaceutical Design, 2024)
Cancer is the second leading cause of global mortality and claims approximately 10 million lives annually. Despite advances in treatments such as surgery, chemotherapy, and immunotherapy, resistance to these methods has emerged. Multidrug resistance (MDR), where cancer cells resist diverse treatments, undermines therapy effectiveness, escalating mortality rates. MDR mechanisms include, among others, drug inactivation, reduced drug uptake, enhanced DNA repair, and activation of survival pathways such as autophagy. Moreover, MDR mechanisms can confer resistance to other therapies like radiotherapy. Understanding these mechanisms is crucial for improving treatment efficacy and identifying new therapeutic targets. Extracellular vesicles (EVs) have gathered attention for their role in cancer progression, including MDR development through protein transfer and genetic reprogramming. Autophagy, a process balancing cellular resources, also influences MDR. The intersection of EVs and autophagy further complicates the understanding of MDR. Both extracellular (exosomes, microvesicles) and intracellular (autophagic) vesicles contribute to therapy resistance by regulating the tumor microenvironment, facilitating cell communication, and modulating drug processing. While much is known about these pathways, there is still a need to explore their potential for predicting treatment responses and understanding tumor heterogeneity.
Keywords: multidrug resistance